Aberrant P-cadherin expression is an early event in hyperplastic and dysplastic transformation in the colon. Issue 4 (1st April 2002) - Hardy, R G; Tselepis, C; Hoyland, J; Wallis, Y; Pretlow, T P; Talbot, I; Sanders, D S A; Matthews, G; Morton, D; Jankowski, J A Z
Abstract : Background: Colorectal adenomatous and, probably, hyperplastic polyp development requires epithelial remodelling and stratification, with loss of E-cadherin expression implicated in adenoma formation. We have shown that P-cadherin, normally expressed in stratified epithelia and placenta, is aberrantly expressed in disturbed epithelial architecture associated with colitis. Aims: (i) To investigate the role of P-cadherin in colonic polyp formation. (ii) To ascertain whether expression of P-cadherin is independent of or correlated with expression of its associated proteins— E-cadherin, β-catenin, and γ-catenin. (iii) To determine if P-cadherin is functional regarding catenin binding in polyps. Methods: Expression and localisation of cadherins (E- and P-) and their associated catenins (β- and γ-) were determined in aberrant crypt foci (ACF), in polyps with hyperplastic morphology (hyperplastic polyps and serrated adenomas), and in adenomatous polyps by immunohistochemistry, western blotting, and mRNA in situ hybridisation. Assessment of cadherin-catenin binding was evaluated by co-immunoprecipitation. Adenomatous polyposis coli (APC) mutation was assessed in adenomatous polyps. Results: P-cadherin was expressed from ACF through to hyperplastic and adenomatous polyps. Alterations in E-cadherin and catenin expression occurred later, with variant patterns in (i) ACF, (ii) hyperplastic polyps and serrated adenomas, and (iii) adenomatous polyps. P-cadherin present in adenomas was functional with regard to catenin binding, and its expression was independent of APC mutational status. Conclusions: P-cadherin is aberrantly expressed from the earliest morphologically identifiable stage of colonocyte transformation, prior to changes in E-cadherin, catenin, and APC expression/mutation. P-cadherin expression alone does not predict tissue morphology, and such expression is independent of that of associated cadherins and catenins.